Mission as "saving" abandoned infants in Johannesburg inner city: An evaluation of the Door of Hope Mission - Mangayi, Lukwikilu C. (HTS teologiese studies, 2019)
In this study, I position the Door of Hope (DoH), an organisation which attempts to work with abandoned and orphaned children, as a faith-based organisation and attempt to determine its effectiveness in relation to missio Dei [the mission of God]. This evaluation focussed on the four different ‘mission orientations’ that a religious community could have in society. Insights gained through this scrutiny of DoH highlight the notion that faith-based organisations in areas such as the inner city of Johannesburg in South Africa can genuinely embrace God’s mission as co-workers in God’s mission to realise a transformed reality symbolised by shalom or collective well-being of all of creation, in particular, for the most vulnerable citizens of Johannesburg inner city, such as infants and young women at risk.